2021
DOI: 10.3389/fpsyg.2021.706168
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mental Health and Hostility Are Associated With Longitudinal Increases in Child Internalizing and Externalizing Problems During COVID-19

Abstract: Children are at high risk for negative COVID-19 related outcomes. The present longitudinal study assessed (1) changes in child internalizing and externalizing problems from before to during the pandemic and (2) whether parent mental health (depression, anxiety, stress) or parenting behavior during COVID-19 were associated with changes in child mental health problems. Sixty eight mother-child dyads participated in this study. Children were approximately five years-old at the time of enrollment and were between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 49 publications
6
47
0
2
Order By: Relevance
“…Parenting behaviors such as maternal hostility, physical and emotional neglect, low levels of warmth/sensitivity, and psychological distress (e.g., anxiety, depressive symptoms) have been consistently associated with child externalizing problems, and to a lesser extent, with child internalizing problems (Pinquart, 2017 ; Hecker et al, 2019 ; Bellina et al, 2020 ; Khoury et al, 2021 ; Yan et al, 2021 ). Indeed, hostile parenting and psychological distress have been more systematically linked with externalizing problems compared to internalizing problems (Stone et al, 2016 ; Khoury et al, 2021 ; Yan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenting behaviors such as maternal hostility, physical and emotional neglect, low levels of warmth/sensitivity, and psychological distress (e.g., anxiety, depressive symptoms) have been consistently associated with child externalizing problems, and to a lesser extent, with child internalizing problems (Pinquart, 2017 ; Hecker et al, 2019 ; Bellina et al, 2020 ; Khoury et al, 2021 ; Yan et al, 2021 ). Indeed, hostile parenting and psychological distress have been more systematically linked with externalizing problems compared to internalizing problems (Stone et al, 2016 ; Khoury et al, 2021 ; Yan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parenting behaviors such as maternal hostility, physical and emotional neglect, low levels of warmth/sensitivity, and psychological distress (e.g., anxiety, depressive symptoms) have been consistently associated with child externalizing problems, and to a lesser extent, with child internalizing problems (Pinquart, 2017 ; Hecker et al, 2019 ; Bellina et al, 2020 ; Khoury et al, 2021 ; Yan et al, 2021 ). Indeed, hostile parenting and psychological distress have been more systematically linked with externalizing problems compared to internalizing problems (Stone et al, 2016 ; Khoury et al, 2021 ; Yan et al, 2021 ). Research underscoring the interlock between maternal psychological distress and child externalizing problems (Yan et al, 2021 ) suggests that maternal psychological distress is associated with more erratic and unpredictable parenting behaviors (Dubois-Comtois et al, 2013 ), which could amplify child externalizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Parents have reported increased mental health concerns relative to non-parent adults (Gadermann et al, 2021 ; Pierce et al, 2020 ), particularly depression and anxiety (Cameron et al, 2020 ; Feinberg et al, 2021 ). Research on child mental health during the pandemic has shown impacts in terms of increased behavior problems (externalizing) as well as depression and anxiety symptoms (internalizing) (Feinberg et al, 2021 ; Glynn et al, 2021 ; Khoury et al, 2021 ; Waller et al, 2021 ). At the same time, a few studies have also demonstrated reductions, no change, or both increases and decreases in youth mental health symptoms (e.g.…”
mentioning
confidence: 99%
“…Poor parent mental health prior to the pandemic has also been associated with children’s internalizing and externalizing during the pandemic (Fosco et al, 2021 ). In another longitudinal study, maternal anxiety was associated with greater increases in child internalizing behaviors during the pandemic, and parent hostility was associated with greater increases in child externalizing behaviors (Khoury et al, 2021 ). More family routines during the pandemic have been associated with fewer internalizing and externalizing problems in children (Glynn et al, 2021 ), and greater family functioning has also been associated with fewer mental health problems in youth during the pandemic (Penner et al, 2021 ).…”
mentioning
confidence: 99%
“…Hong et al, 2018;Schelble, Franks, & Miller, 2010), 양 육행동 (Barnett, Gustafsson, Deng, Mills-Koonce, & Cox, 2012;Lim, 2019), 가정환경(Y.-J. Hong, Kang, Lee, & Choi, 2017;Kao, Tuladhar, & Tarullo, 2020) (Khoury, Kaur, & Gonzalez, 2021;Tso et al, 2020), 개인에 게 미치는 신체적, 재정적, 정서적 측면 등 한 측면에 초점을 맞추어 살펴보는 등 (Brown, Doom, Lechuga-Peña, Watamura, & Koppels, 2020;Ravens-Sieberer et al, 2021), 코로나19 상황을 다 면적 측면에서 통합적으로 살펴보려는 시도는 부족하다. 특 히 개인은 객관적인 역경이나 어려운 상황을 경험할 때 이를 주관적으로 인식하고 평가하며, 개인의 성격, 기질과 개인이 처한 맥락에 따라 각기 다른 방식으로 대처하는 경향이 있다 (Lazarus & Folkman, 1984).…”
unclassified